Telemonitoring as an extension of postoperative care in intestinal ostomy patients (Research, Society and Development, 2022)
Objective: To identify the sociodemographic and health profiles and the need for guidance in the postoperative period of patients undergoing surgery to make an intestinal ostomy in a University Hospital in the State of Rio de Janeiro, as well as to propose the implementation of a telemonitoring service. Methodology: this is a descriptive, exploratory research with a qualitative approach. The sample consisted of 25 participants, from February to August 2021. Data collection was carried out in three stages. First, a descriptive analysis was carried out, followed by an inferential analysis to verify the variation in the proportion of care provided to ostomized patients in telemonitoring using the corrected McNemar test. The significance criterion adopted was the level of 5%. Statistical analysis was processed using SPSS version 26 software. Results: The analysis highlighted that neoplasms have a higher prevalence among the causes that lead to the creation of an intestinal ostomy, representing (92.0%) of the sample. Considering both sexes, in relation to the profile of needs, the patients had a significantly positive response rate after telemonitoring. The evaluation of telemonitoring demonstrates that the calls helped in the orientation and care of the intestinal ostomy. Conclusion: The study carried out was relevant and contributed to the appropriation of telemonitoring technology as an extension of care.